If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -8) = -35 Reorder the terms: 7(-8 + x) = -35 (-8 * 7 + x * 7) = -35 (-56 + 7x) = -35 Solving -56 + 7x = -35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 7x = -35 + 56 Combine like terms: -56 + 56 = 0 0 + 7x = -35 + 56 7x = -35 + 56 Combine like terms: -35 + 56 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 9(x+7)=99 | | k^2+8k=105 | | 0=6x^2+6x-36 | | 2x^2-6x-36=0 | | 12-8x=81-29x | | 6x-2=8x+4 | | h(t)=-16t^2+63t+4 | | 5+2(x+3)=10-(3x-13) | | P-167=321 | | 180=j-24 | | 125-2x=5x+20 | | -0.875m=0.25 | | 1.7u=0.2 | | =x^2-5x-6 | | K-32=217 | | 0.75y=-0.5 | | 4p+14=11p | | 0.25x+5=9 | | 150+y=879 | | -3=0.4v | | 91=x+52 | | -3=0.4 | | x=(x+1)(x+y) | | 5=0.6w | | 7x+38=-5x-10 | | W+233=319 | | -1.5d=8 | | D-67=23 | | 840=45+f | | y^2-5= | | 314+z=350 | | 0.6x=-4 |